A Contrastive Study of Conceptual Metaphor of Love in English an Vietnamese Songs in the 20th Century - Hà Lê Hồng Hoa (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Investigating the conceptual metaphors of love in English and Vietnamese 20th century songs; Finding out the similarities and differences in linguistic and cultural features of love through conceptual metaphor used in the song lyrics of the two countries; Helping Vietnamese learners of English and English learners of Vietnamese learn English and Vietnamese better and helping the listeners have a better insight into the lyrics of the songs through the conceptual metapho